กรอบแนวคิดของแผนแบบการสุ่มตัวอย่างแบบอันดับ - ศักดิ์ระพี อินซีอาจ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The objective of this study is to study conceptual framework of ranked set sampling and compare the sampling method between simple random sampling (SRS) with ranked set sampling (RSS). The relative efficiency (R.E.) was used as the criteria for evaluation for precision of both method. The ranked set sampling is balanced ranked set sampling without replacement. The two sampling method had been compared the efficiency in term of accuracy for mean estimators. The conceptual framework of ranked set sampling has been developed from simple random sampling. The objective of ranked set sampling was to fine a more efficient method to estimate population mean. Ranked set sampling is more suitable when the variance of population is extreme value and the actual measurement of the variable of interest which is costly and/or time-consuming. The comparison of the relative efficiency show that the relative efficiency is more than one. That mean ranked set sampling is more efficiency than simple random sampling based on equal sample size.